(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluating the effectiveness of motor rehabilitation in children with sequelae of encephalitis according to Traditional Medicine. Subjectives: Sixty pediatric patients aged ≤ 6 years were diagnosed with sequelae of encephalitis after the acute phase, including motor and mental sequelae with manifestations of motor paralysis Methods: Clinical intervention, pre- and post-treatment comparison, without a control group. Pediatric patients were classified according to two Traditional Medicine disease types: Yin deficiency and Qi and Blood deficiency. The children underwent a 6-week course of massage and acupressure combined with nursing care. Assessment criteria included the Henry scale and developmental index (DQ) according to the Denver II test. Results: Before intervention, the Yin deficiency type was predominant (73.3%); the Yin deficiency type had milder paralysis than the Qi and Blood deficiency type (grade IV paralysis accounted for 13.6% compared to 62.5%). After 6 weeks of intervention, motor function improved significantly in both groups (p < 0.05). The Yin deficiency type showed better recovery: the percentage of gross and fine motor development indices returning to normal levels was 45.5%, while in the Qi and Blood deficiency type it was 37.5% and 12.5%, respectively Conclusions: Acupressure combined with nursing care has a good recovery rate in both disease types, with the Yin deficiency type having a better prognosis for functional recovery and developmental indicators compared to the Qi and Blood deficiency type